Müllerian Cyst of the Vagina Masquerading as a Cystocele - Emrah Töz; Muzaffer Sancı; Süheyla Cumurcu; Aykut Özcan (Case Reports in Obstetrics and Gynecology)
Müllerian cysts are usually small, ranging from 0.1 to 2 cm in diameter. Rarely, they may be enlarged and mistaken for other structures, such as a cystocele or urethral diverticulum. We report on a female with symptomatic vaginal wall prolapse, diagnosed as a vaginal Müllerian cyst, which was originally misdiagnosed as a cystocele. The mass was soft and could be compressed manually without difficulty. Perineal ultrasonography and cystoscopy revealed no relationship between the cyst and the lower urinary tract, suggesting independence of the lesion. We performed surgical treatment with complete excision of the mass via a vaginal approach under spinal anaesthesia. The pathology result confirmed a benign Müllerian cyst lined with mucinous and squamous epithelium. When evaluating an anterior vaginal cyst, assessment of the lesion via history taking and pelvic examination is important to confirm both lesion size and location. Perineal ultrasonography performed with an empty bladder is useful to differentiate such vaginal cysts and to define their communication, if any, with adjacent organs.